Characterization of Solvent-Treated PEDOT:PSS Thin Films with Enhanced Conductivities - Rwei, Syang-Peng (Polymers (Basel), 2019)
The conducting polymer of poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) is one of the most important and intensively investigated organic conducting materials. The PEDOT:PSS water dispersions with various concentrations of poly (4-styrenesulfonic acid) solution (PSSAS) were synthesized by 3,4-ethylenedioxythiophene (EDOT) in the presence of water. The fabrication of the solvent-treated PEDOT:PSS films through spin coating and solvent treatment processes was achieved with a solvent of pure water mixed with acetone (or MeOH, EtOH) in a ratio of 50:50. Moreover, both the organic solvent and water have synergetic effects while the PSS and PEDOT-attached PSS segments will form a coil-like and a linear (or extended-coil) structure, respectively. That may induce a stacking of the linear and planar PEDOT-attached PSS segments, which favors the formation of a crystalline phase. Finally, the maximum electrical conductivity of the PEDOT:PSS thin films with solvent treatment was investigated by means of X-ray diffraction (XRD) patterns and scanning electron microscope (SEM) images. Furthermore, we aimed to explain the synergetic effects of phase separation of the PEDOT:PSS thin films by both the organic solvent and water.